Efektivitas Discovery Learning dalam Meningkatkan KPS Materi Elektrolit dan Non Elektrolit Ditinjau Jenis Kelamin - Indah Rahmawati; Ila Rosilawati; Noor Fadiawati (Universitas Lampung, 2018)
This research was aimed to describe the effectiveness of discovery learning model to improve science process skills (SPS) on electrolyte and non electrolyte topic related to gender. The method of the research was quasi experimental with 2x2 factorial design. Population was all students of class X IPA senior high school in Bandarlampung on academic year 2017/2018. Samples in this study were students of X IPA 3 as experimental class and students of X IPA 1 as control class which obtained by using purposive sampling technique. The statistical analysis used two ways ANOVA and descriptive analysis. The result of the research showed that no interaction between the use of discovery learning model with gender on student’s SPS, discovery learning model was effective to improve the SPS, the percentage of male students with high n-gain categories is higher than the percentage of female students. Penelitian ini bertujuan mendeskripsikan efektivitas model discovery learning dalam meningkatkan keterampilan proses sains (KPS) pada materi larutan elektrolit dan non elektrolit ditinjau dari jenis kelamin. Metode dalam penelitian ini menggunakan metode kuasi eksperimen dengan desain faktorial 2x2. Populasi dalam penelitian ini adalah seluruh siswa kelas X IPA SMA Negeri Bandarlampung Tahun Pelajaran 2017/2018. Sampel dalam penelitian ini adalah siswa kelas X IPA 3 sebagai kelas eksperimen dan siswa kelas X IPA 1 sebagai kelas kontrol yang diperoleh dengan menggunakan teknik purposive sampling. Analisis statistik menggunakan ANOVA dua jalur dan analisis deskriptif. Hasil penelitian menunjukkan bahwa tidak ada interaksi antara penggunaan model discovery learning dengan jenis kelamin terhadap KPS siswa, model discovery learning efektif untuk meningkatkan KPS, persentase siswa laki-laki yang memiliki kategori n-gain tinggi lebih tinggi daripada persentase siswa perempuan.Kata kunci: jenis kelamin, elektrolit dan non elektrolit, KPS, model discovery learning